IT governance and information security : guides, standards and frameworks /: guides, standards and frameworks. (2021) - Maleh, Yassine, 1987-; Sahid, Abdelkebir, 1983-; Alazab, Mamoun, 1980-; Belaissaoui, Mustapha, 1968-
No abstract available